2021
DOI: 10.21608/ejhm.2021.160884
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study between Different Additives to Levobupivacaine in Caudal Block for Postoperative Pain Management in Pediatrics Undergoing Hypospadias Repair: Randomized Controlled Study

Abstract: Background: For both children and their caregivers, postoperative pain is an irritating experience. Several approaches have been used to treat postoperative pain in pediatric patients improving sleep quality, and extending sedation time. Objectives: This work aimed to compare the postoperative analgesic effect and any complications of addition of one of these drugs nalbuphine versus fentanyl versus dexamethasone to levobupivacaine in caudal block (CB) in pediatric patients undergoing hypospadias repair. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…Intraoperative SpO 2 was not statistically significant between the Group A and Group B (P>0.05) according to El Shamaa and Ibrahim. 15 Hassan et al, 5 observed FLACC scores from 30 min to 12 h postoperatively. There was a significant difference between the group N(0.25% levobupivacaine 0.75 mL/kg+0.2 mg/kg nalbuphine+normal saline), Group F (0.25% levobupivacaine 0.75 mL/kg+1 μg/kg fentanyl) and Group D (0.25% levobupivacaine 0.75 mL/ kg+0.1 mg/kg dexamethasone+normal saline) at 2, 6, and 8 h postoperatively; otherwise, no significant difference was found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraoperative SpO 2 was not statistically significant between the Group A and Group B (P>0.05) according to El Shamaa and Ibrahim. 15 Hassan et al, 5 observed FLACC scores from 30 min to 12 h postoperatively. There was a significant difference between the group N(0.25% levobupivacaine 0.75 mL/kg+0.2 mg/kg nalbuphine+normal saline), Group F (0.25% levobupivacaine 0.75 mL/kg+1 μg/kg fentanyl) and Group D (0.25% levobupivacaine 0.75 mL/ kg+0.1 mg/kg dexamethasone+normal saline) at 2, 6, and 8 h postoperatively; otherwise, no significant difference was found.…”
Section: Discussionmentioning
confidence: 99%
“…Levobupivacaine is a long-acting amide local anesthetic levobupivacaine is slightly less toxic to the central nervous system than bupivacaine, and it causes less myocardial depression and fatal arrhythmias. 5 Dexamethasone is very effective in prolonging the duration of peripheral nerve blocks, it also improves the quality of sensory blocks. Dexamethasone is commonly used for the management of post-operative pain, nausea, and vomiting.…”
Section: A Comparative Study Of Levobupivacaine Alone and In Combinat...mentioning
confidence: 99%